Exploring Racial Disparities in Mental Health Diagnoses and Neighborhood Disorganization Among an Urban Cohort of Children and Adolescents with Chronic Medical Conditions - Anne Elizabeth Glassgow; Michael Gerges; Marc Atkins; Molly Martin; Rachel Caskey; Krista Sanders; Mansha Mirza; Benjamin Van Voorhees; Sage Kim (Mary Ann Liebert, 2019)
Objective: This article describes the demographic distribution of, and association between, neighborhood disorganization and mental health diagnosis by race in a large cohort of urban children with chronic medical conditions. Methods: Data for this study were from Coordinated Healthcare for Complex Kids (CHECK), a health care demonstration project funded by the Center for Medicare and Medicaid Innovation. We conducted regression analyses to examine the relationship between neighborhood disorganization and mental health diagnosis among 6,458 children enrolled in CHECK. Results: The most common mental health diagnoses were mood disorders (8.6%), Attention-Deficit/Hyperactivity Disorder (7.4%), conduct disorders (6.1%), and anxiety disorders (4.8%). Black children had the highest neighborhood disorganization scores compared with other racial/ethnic categories. However, Black children had the lowest proportion of mental health diagnoses. Lower neighborhood disorganization was associated with having a mental health diagnosis; however, when adding race/ethnicity to the model, neighborhood disorganization no longer was significant. Conclusions: Level of neighborhood disorganization was highly correlated with racial/ethnic composition of the neighborhoods, and Black children disproportionately resided in highly disorganized neighborhoods compared with other groups. Neighborhood disorganization may not have sufficient variability within the racial/ethnic categories, which may explain the absence of an interaction between race/ethnicity and mental health diagnosis.